PENGARUH KADAR AIR TERHADAP KUAT GESER PADA TANAH LANAU - Endaryanta Endaryanta (Universitas Negeri Yogyakarta, 2006)
Landslide disaster such as bank slide or embankment slide often occurs.This it begins with a simple problem, that is infiltration of rain water into soilcausing the decrease of soil strength resulting in collapse. The research triesto explain the water influe'nce at the shear strength of soil to find out how muchwater content may induce soil collapse.This experimental research was conducted in the soH laboratory usingmud from Imogiri, Bantul conditioned in several water contents (from 10% to500/0) and direct shear tests were then applied. This experiment would produceCD (internal soil shear angle), c (soil cohesion), and finally slide off soil safetyfactor (F).This research has resulted:1. at a low water content (10%) the CD soil is low, the CD increases by increasingthe water content, but the next increas of water' content causes a decreaseof CD. The maximum CD (32.5°) reaches at 23% of water content.2. at a low water content (10%) the c soil is low, the c increases by increasingthe water content, but the next increasing of water content causes a decreaseof c. The maximum c (0.076 kg/cm2) reaches at 22% of water content.3. at a low water content (100/0) the F soil is low, the CD increases by increasingthe water content, but the next increasing of water content causes a decreaseof F. The maximum F reaches at 21% of water content.Key words: mud, soil, water content, shear strength, cohesion, land slide.